Política educacional no Brasil: proposições educacionais no plano plurianual dos governos Lula e Dilma Rousseff (2008-2011) - Michelon, Edimor Antônio (2014)
This study it analyzes the flexibilizações of the implemented educational politics from the educational proposals in the plurianual plan of the Lula governments and Dilma Rousseff, considering that in result of the tensions and pressures of classroom, delineated (2008-2011) and circumscribed educational politics emerge socially, in the context of the economic development considered and supported by the Brazilian State, in the axles norteadores, presented in the educational field for the Plan of Development of Educação (PDE), Plan of Goals Commitment All for Education and Plan of Articulated Actions (PAIR), and in the economic field for the Plurianual Plan Development with Social Inclusion and Education of Quality and the Plan of Acceleration of the Growth (the CAP I). The plans, programs and projects that emerge of the plurianual plan, constitute one educational politics of productive matrix, for the form as it articulates and it mobilizes diverse agencies and mechanisms of State. In this direction they are the programs of Digital Inclusion, Health in the School, More Education, Innovative Average Education, Support to the Pertaining to school Transport, Way of the School and Professionalized Brazil, among others. This category of intersetorial politics sets in motion mechanisms that dialogue between itself, in order to synthecize action that they at risk minimize the conflicts unchained for the population groups, for the insufficience of the ways, for the proper immediate social production. In this direction, the considered educational programs from the plurianual plan, represent in the flexibilizações of the social politics, the tensions and pressures that disclose the relations between classrooms in a similar way. Considering the educational politics in Brazil analyzed in this study, we can identify that they show as half specific of the economic-financial and politician-ideological production, arrangements and as mediações of the tensions and pressures between classrooms. The necessary historical conditions to the individuals cannot be disrespected in analyze of the fight of classrooms, considering that of the insufficience and incapacity of immediate social production, tensions and promotional pressures of conflicts emerge. The intersetorial and inter-ministerial joint is the expression and the representation of the State in the arrangement form and mediation of the conflicts between classrooms. The implementation of plurianuais plans constitutes one of these intergovernamentais forms of joint that are not indissociáveis of the politician-productive set and arcabouço economic-financial that flexibiliza and delineate the programs, plans and projects implemented for the State in the governments Lula and Dilma Rousseff (2008-2011) for the Brazilian education